Clinicopathologic characteristics and prognosis of basaloid squamous cell carcinoma of the rectum in comparison with adenocarcinoma: a retrospective cohort study - Zhou, Yanyang; Chang, Yi; Guo, Haixia; Fan, Yanwei; Wang, Shijie (Frontiers in Oncology, 2025)
ObjectiveBasaloid squamous cell carcinoma (BSCC) is a rare histological subtype of rectal cancer. This study aimed to investigate the clinicopathologic features and survival outcomes of primary rectal BSCC and to compare them with those of adenocarcinoma (AD).MethodsPatients diagnosed with rectal BSCC and AD patients were identified from the Surveillance, Epidemiology, and End Results database from 2000 to 2019. Univariable and multivariable Cox regression analyses were performed to identify potential risk factors for survival in BSCC patients. A nomogram was constructed to predict the prognosis of BSCC patients.ResultsA total of 257 BSCC and 77,094 AD patients were identified. BSCC patients were more significantly correlated with female gender, early clinical stage, and poor differentiation. Significantly better 5-year overall survival (OS) and cancer-specific survival (CSS) were observed in patients with BSCC than those with AD (OS: 60.4% vs. 52.0%, p = 0.041; CSS: 63.4% vs. 54.5%, p = 0.042). This survival difference still persisted in multivariable analysis [OS: hazard ratio (HR) = 0.269, p < 0.001] and after propensity score matching (OS: HR = 0.387, p < 0.001). For BSCC patients, multivariable analysis indicated that advanced clinical stage was associated with worse OS and CSS and that surgery and chemotherapy were associated with better OS and CSS.ConclusionPatients with rectal BSCC have significantly better survival outcomes than those with rectal AD, with a more early clinical stage. Surgery in combination with chemotherapy is the preferred treatment to improve prognosis.